2020
DOI: 10.1093/nar/gkaa565
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory functions of the glucocorticoid receptor require DNA binding

Abstract: Abstract The glucocorticoid receptor is an important immunosuppressive drug target and metabolic regulator that acts as a ligand-gated transcription factor. Generally, GR’s anti-inflammatory effects are attributed to the silencing of inflammatory genes, while its adverse effects are ascribed to the upregulation of metabolic targets. GR binding directly to DNA is proposed to activate, whereas GR tethering to pro-inflammatory transcription factors is thought to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…2a ). A similar effect has been observed on a recent report comparing GRwt and a DBD binding mutant in primary mouse embryonic fibroblast cells 25 . A closer inspection revealed that only 43 genes (out of 13,465) are differentially regulated (using a 0.6 log 2 FC and 0.001 FDR) between GRwt and GRmon backgrounds, with only 5 genes overlapping with hormone-dependent action.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…2a ). A similar effect has been observed on a recent report comparing GRwt and a DBD binding mutant in primary mouse embryonic fibroblast cells 25 . A closer inspection revealed that only 43 genes (out of 13,465) are differentially regulated (using a 0.6 log 2 FC and 0.001 FDR) between GRwt and GRmon backgrounds, with only 5 genes overlapping with hormone-dependent action.…”
Section: Resultssupporting
confidence: 88%
“…activities 25 . Given the complexity of potential mechanisms of action, a fully dissociated, independent transactivation vs transrepression model requires revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIME (Rapid Immunoprecipitation Mass spectrometry of Endogenous proteins) with isobaric labelling has been successfully applied to identify protein interactions of estrogen receptor alpha and other TFs in breast cancer cells ( 81 , 82 ). Moreover, GR interactome has been recently investigated by ChIP coupled with MS (ChIP-MS) in mouse liver and mouse embryonic fibroblasts ( 83 ). Here, we utilized ChIP-SICAP ( 18 ), a novel proteomic methodology, to cast new light to the protein associations and chromatin function of GR, an important NR and drug target that has been widely studied for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Following GR binding, gene activation -involving recruitment of coactivators and chromatin remodellers -occurs at sites of pre-established enhancer-promoter interactions, with the presence of GR increasing the frequency of productive interactions (8). In contrast, the mechanism by which GR downregulates gene expression remains an area of considerable debate, with evidence for protein-protein tethering, indirect mechanisms of action, and GR binding to negative or cryptic response elements presented (9)(10)(11)(12)(13)(14). Surprisingly for a transcription factor which is so widely expressed, GR action is remarkably context-specific.…”
Section: Introductionmentioning
confidence: 99%